Pengaruh Struktur Kepemilikan terhadap Kinerja Finansial dan Operasional, Keunggulan Daya Saing Berkelanjutan Berdasarkan Reputasi Ukuran Akuntansi, dan Kinerja Pasar (Studi pada BUMN Tbk) - Lubis, Tona Aurora; Salim, Ubud; Djumahir, Djumahir; Sudarma, Made (Universitas Brawijaya, Indonesia, 2011)
This research analyzes and explains comprehensively the effects of ownership structure on financial and operational performance, on sustainable competitive advantage based on accountancy measurement reputation, and on market performance in Indonesia's privatized SOEs (BUMN Tbk). The samples of this study were selected using the purposive sampling method with the type judgment sampling. The criteria for sample selection were: privatized SOEs which are non-backing sector, privatized SOEs having state owned stock/share more than 51%, and privatized SOEs doing Initial Public Offering (IPO) before 2007. The samples of this research were 9 privatized SOEs. The data analysis was conducted using inferential statistic analysis. Inferential statistical analysis used Structural Equation Modeling (SEM) causality based on components or variance. SEM causality analysis, known as Partial Least Square (PLS), is performed using SmartPLS version 1.10 software. The research result shows that: (1) the increase of public ownership in ownership structure can improve financial and operational performance; (2) the increase of public ownership in ownership structure can improve sustainable competitive advantage based on accountancy measurement reputation; (3) the increase of public ownership in ownership structure is unable to improve market performance; (4) the improvement in financial and operational performance can improve market performance; (5) the improvement in financial and operational performance can sustainable competitive advantage based on accountancy measurement reputation; and (6) the improvement of sustainable competitive advantage based on accountancy measurement reputation is unable to improve market performance.